All‐trans retinoic acid improves goat oocyte nuclear maturation and reduces apoptotic cumulus cells during in vitro maturation. (5th May 2014) - Pu, Yong; Wang, Zhangfan; Bian, Yani; Zhang, Fei; Yang, Pan; Li, Yunsheng; Zhang, Yunhai; Liu, Ya; Fang, Fugui; Cao, Hongguo; Zhang, Xiaorong
Abstract All‐trans retinoic acid (t‐RA) is a natural component and representative physiologically active metabolite of vitamin A, having multiple physiologic functions. The objective of this study was to evaluate the effect of t‐RA on goat oocyte maturation and cumulus cell apoptosis during in vitro maturation (IVM). Immature goat cumulus‐oocyte complexes (COCs) were matured in vitro in the absence or presence of t‐RA at concentrations of 10 nmol/L, 100 nmol/L and 1000 nmol/L. Oocyte maturation and embryo development were assessed by polar body formation and parthenogenetic activation, respectively. Oocyte survival was checked by Trypan blue staining. Apoptosis of cumulus cells was analyzed by terminal deoxynucleotidyl transferase nick end labeling staining and quantitative real‐time PCR. In comparison with the control group, 100 nmol/L and 10 nmol/L t‐RA significantly improved goat nuclear oocyte maturation and survival (P < 0.05). Addition of 1000 nmol/L t‐RA improved nuclear maturation (P < 0.05), but had no effect on survival of goat oocytes. t‐RA had no positive effect on goat parthenogenetic embryonic cleavage, blastocyst formation or total cell numbers. However, t‐RA inhibits the apoptosis of cumulus cells (P < 0.01). t‐RA treatment up‐regulated the expression of B‐cell lymphoma 2 (BCL‐2), catalase (CAT) (P < 0.05) and down‐regulated the expression of Caspase‐8 (P < 0.05). In conclusion, t‐RA has positive effects on goat oocyte nuclear maturation and reduces apoptotic cumulus cells during IVM.